Grade 10 Namibian learners' problem-solving skills in algebraic word problems - Hesekiel K. Iilonga; Ugorji I. Ogbonnaya (Jurnal Infinity, 2023)
This study investigated Grade 10 Namibian learners' problem-solving skills in algebraic word problems. A sample of 351 Grade 10 learners from ten secondary schools in the Ohangwena Region in Namibia participated in this study. The study followed a qualitative approach and adopted Polya's Problem-Solving Model as the framework. The data were collected using the Algebra Word Problem-solving Test and Interview. The findings showed that the learners needed better problem-solving skills in algebraic word problems. Only 6% and 7% of the learners showed an ability to understand the problems and devise a plan, respectively, while only 5% could carry out the plans. Based on the findings, it is recommended that teachers introduce learners to Polya's steps of problem-solving and incorporate word problems into mathematics teaching.